Initially concealed concussion lowers in-game performance of NCAA Division I football players: a case series. Issue 1 (2nd January 2021) - Monseau, Aaron J.; Balcik, Brenden J.; Roberts, Luke; Andrews, Reed; Sharon, Melinda J.
ABSTRACT: Objectives : Many athletes conceal concussion symptoms to continue to play. If athletes and coaches knew that performance drops significantly after a concussion, in turn hurting the team, athletes may be more prone to report concussion symptoms. The objective of our research was to report three cases that support this performance decline after an undisclosed concussion. Methods : This is a case series of three NCAA Division I football players who did not immediately report their concussions. The play in which the concussion occurred was identified via video review then the players' pre and post-injury performance grades, as scored by their position coaches, were recorded. Additional data regarding their performance in other games and their concussion assessments were also recorded. Results : Three injuries were identified and reviewed. Player 1 had a pre-injury performance score of 76/100 with a post-injury score of 47/100. This was a drop of 29 points for a decrease in his in-game performance by 38%. Player 2 had a pre-injury score of 100/100 with a post-injury score of 60/100. This was a drop of 40 points or a 40% decrease in his in-game performance. Player 3 had a pre-injury score of 67/100 and a post-injury score of 43/100 for a drop of 24 points or a 36% decrease in his in-game performance. Conclusions : We reported three college football players who suffered concussions but did not immediately disclose their symptoms. Each had a marked decrease in performance grades after their concussion. If the performance effect of a concussion can be quantified, athletes and coaches may begin to change their mind-set that a concussion can be 'played through.' This case series should serve as a first step in quantifying concussion effects on performance.